Eggs Martabak Training With Shirataki to Students SMKN 7 Tangerang - Ira B Hubner; Juliana Juliana; Daphne Sweet Chandra; Imelda Joanna (CV. AGUSPATI RESEARCH INSTITUTA, 2021)
Published The Covid-19 condition in the world has had a bad impact on everyone, which is detrimental to all parties in terms of health and the economy. The Covid-19 virus is deadly, so people with low immunity will be vulnerable to contracting it. Due to the fairly rapid transmission factor, this has caused some schools to have to do independent online learning, and some employees have to do work from home. Some of the preventions that we can do are to maintain our health by consuming healthy and low-calorie foods. Community Service is one of the student activities of the Faculty of Tourism, Pelita Harapan University, as evidence of caring for the community by providing knowledge and skills that can be done at home. Through this PkM activity, we will provide a menu of Indonesian dishes that can be tried and processed while at home, making shirataki egg martabak. Egg martabak, which generally contains meat, this time the team will replace the meat filling by including shirataki in it. The use of shirataki as a substitute for this meat will make a difference in terms of variety. Besides having a more chewy texture, this shirataki martabak is also healthy because the calorie content of shirataki is quite low.Shirataki egg martabak is expected to help partners provide new healthy flavor variants because some Indonesian people eat egg martabak using rice. The purpose of this community service activity is (1) To share knowledge and practice skills, (2) to Provide cooking methods and steps to make martabak with Shirataki basic ingredients (3) to provide input to the community to stay healthy. Martabak is unique in its taste and can be easily found. KeywordsMartabak shirataki